The Impact of Financial Literacy and Financial Inclusion towards the Saving Behavior of the Students - Irfan, Irfan; Nasyalia, Cut; Muhyarsyah, Muhyarsyah; Hani, Syafrida; Sari, Maya (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The purpose of this study was to assess and analyze the impact of Financial Literacy and Financial Inclusion on Saving Behavior using Self-Control as a moderator variable at the Department of Accounting, Faculty of Economics and Business, Private Islamic University in Medan City.Methodology: This study takes an associative method. This survey included 3747 students from the Department of Accounting, Faculty of Economics and Business, Private Islamic University in Medan City. The Slovin algorithm was used to sample 97 students from the Department of Accounting, Faculty of Economics and Business, Private Islamic University in Medan City. Data for this study were gathered through observation and questionnaires. This study's data processing processes used a quantitative approach with statistical analysis using the PLS (Partial Least Square) software tool.Findings: The findings of this study show that financial literacy and financial inclusion have a significant effect on saving behavior and that self-control does not moderate the effect of financial literacy and financial inclusion on saving behavior of Department of Accounting students, Faculty of Economics and Business, Private Islamic University in Medan City.Conclusion: This study examines how financial literacy and financial inclusion affect student saving behavior and self-control as a moderating variable. Students are the right generation to implement financial education because students are agents of change with the hope of bringing change in a better direction than before.